Analytical Study of the Economic Reality of the Syrian family during the Crisis (Journal of Hama University, 2020)
Through this research, we sought to identify the economic reality of the Syrian family, by comparing economic factors for the period before the Syrian crisis, that is, before 2011 with one of the years of the crisis. Then we identified the most important economic problems that the family faced during the years of the Syrian crisis, some of which were previously present, and exacerbated by the circumstances of the crisis, while others emerged during it. The Syrian family are affected greatly by the economic reality during the crisis. And we analyzed a number of economic problems resulting from the crisis, the most important of which were: Unemployment, Increase in economic dependency rate, Low standard of living and Purchasing Power with high prices, Poverty, Food insecurity, Shared housing, and families are increasingly dependent on humanitarian aid and remittances. Through the field study, we found that these economic problems exist among the families of the studied sample, but with varying relative importance. In addition, there were significant differences among the range to which the heads of families affected by economic problems, the greatest suffering centered on the problem of the low standard of living with high prices.Based on the above, the research deals with the following points:1-Analyzing some indicators of the economic reality of the Syrian family in general, and in Aleppo in particular, by comparing one of the years before and during the crisis.2-Defining the most important economic problems that the Syrian family faced during the crisis year.3- Determine the range of heads of households which are affected by the studied economic problems.